Crime Prevention, Migration Control and Surveillance Practices : Welfare Bureaucracy as Mobility Deterrent - Nagy, Veronika; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
EU expansion has stoked fears that criminals from the East may abuse freedom of movement to exploit the benefit systems of richer states. This book examines the way in which physical state borders are increasingly being replaced by internal border controls in the form of state bureaucracies as a means of regulating westward migration. The work examines the postmodern effect of globalisation and how ontological anxieties contribute to securitisation and social sorting in Western countries. It discusses the changes in control societies and how targeted surveillance as a geopolitical tool leads to new digitalised mechanisms of population selection. The book presents a casestudy of Roma migrants in the UK to examine the coping strategies adopted by those targeted. The book also critically evaluates the limitations of digitalised bureaucratic systems and the dangers of reliance on virtual data and selection methods.
1. Introduction; 2. Critical theories social sorting and surveillance in a digital welfare labyrinth; 3.Roma, a global ethnic minority; 4. Welfare policy and the new social sorting of Europe; 5. Mediators, protectors and pathfinders invisible players in mobility approaches;6. Accessing benefits abroad; 7. Commodification online social security claims in virtual bureaucracies;10. Conclusion
Includes bibliographical references and index.
Also available in print format.
Keywords: Crime prevention -- Europe; Emigration and immigration law -- Europe; Border crossing -- Europe; Social security -- Europe; Border crossing; Crime prevention; Emigration and immigration law; Social security; LAW / Criminal Law / General; LAW / Emigration & Immigration; Electronic books